1991
DOI: 10.1038/ki.1991.39
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte adhesion molecules in T cell-mediated lysis of human kidney cells

Abstract: The complementary adhesion molecules LFA-1 (CD11a, 18)/ICAM-1 (CD54) and LFA-2 (CD2)/LFA-3 (CD58) have been shown to be important in T cell interaction with lymphoid target cells. The role of these ligand pairs in cytotoxicity against somatic cells is less well established. While LFA-3 is expressed by all cells in the kidney, ICAM-1 expression is low in normal kidneys but is increased in allograft rejection. An in vitro cytotoxicity assay was used to examine the relative importance of the two adhesion ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Although the increased interstitial ICAM-1 is strategically crucial for recruiting inflammatory cells to the interstitium, how an overexpression of ICAM-1 by tubular cells, that is limited to their apical aspects, interacts with interstitial inflammatory cells remains unknown. On the other hand, this distinctive topography of ICAM-1 expression, confirmed in every human or experimental study that documents tubular ICAM-1 upregulation, may facilitate migration of inflammatory cells into tubular epithelial layer and mediate the various tubular cell-inflammatory cell interactions, including cell-mediated cytotoxicity [4, 15, 25, 26, 27, 28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increased interstitial ICAM-1 is strategically crucial for recruiting inflammatory cells to the interstitium, how an overexpression of ICAM-1 by tubular cells, that is limited to their apical aspects, interacts with interstitial inflammatory cells remains unknown. On the other hand, this distinctive topography of ICAM-1 expression, confirmed in every human or experimental study that documents tubular ICAM-1 upregulation, may facilitate migration of inflammatory cells into tubular epithelial layer and mediate the various tubular cell-inflammatory cell interactions, including cell-mediated cytotoxicity [4, 15, 25, 26, 27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, altered expression of integrins and the immunoglobulin molecules intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) on parenchymal cells may contribute to cytotoxic interactions with infiltrating inflammatory cells [4, 5]. Altered expression of ICAM-1 and VCAM-1 in glomerular, tubulointerstitial, and vascular compartments has been reported in a variety of human kidney diseases and in experimental animal models of renal disease [2, 3, 6, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the factors that induce B7-H1 expressionin vivo were not clarified at present. Previous data have revealed that under inflammatory conditions, the release of proinflammatory cytokines such as TNF-α, IFN-γ, MCP-1 or RANTES was induced by TECs, and those proinflammatory factors could induce or augment the expression of a range of molecules such as MHC-II antigen [27], ICAM-1 [28], VCAM-1 and LFA-3 [29, 30]. Here we also found B7-H1 was induced to express on TECs by the stimulation of some inflammatory factors such as IL-1α, TNF-α or IFN-γ in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured PTEC produce proinflammatory cytokines such as TNFα, MCP-1 and RANTES that can induce or augment the expression of a range of molecules which regulate cellular immunogenicity. These include class I and II MHC antigens [17]and the adhesion molecules intercellular adhesion molecule-1 (ICAM-1) [24, 25], vascular cell adhesion molecule-1 (VCAM-1) [26]and lymphocyte function associated antigen-3 (LFA-3) [27]. This shows that PTEC express several cytokines, costimulatory and adhesion molecules under inflammatory conditions leading to the progression of renal diseases.…”
Section: Introductionmentioning
confidence: 99%